Clarifying the typification of the name Kalanchoe orgyalis (Crassulaceae subfam. Kalanchooideae) - Smith, Gideon F.; Figueiredo, Estrela (Phytotaxa, 2022)
When describing Kalanchoe orgyalis Baker (1882: 110) [Crassulaceae subfam. Kalanchooideae, Kalanchoe Adanson (1763: 248) subg. Kalanchoe] (Figs 1 & 2), Baker cited two collections, “Baron 105! 249!”, both of which were therefore collected by Reverend Richard Baron (1847–1907), with both presumably originating from “West Betsileo, on stony ground and about woods” (Baker 1882: 110), in Madagascar. Baron, at the time a missionary with the London Missionary Society, spent about 35 years in Madagascar and, apart from his evangelical work, was also a proficient naturalist (Dorr 1997: 28–29, Smith & Figueiredo 2021a). Herbarium material that Baron collected in Madagascar mostly made its way to the Royal Botanic Gardens, Kew, from where the novel material was described (Smith & Figueiredo 2021a: 195).